A process evaluation of the WHiTE Two trial comparing total hip arthroplasty with and without dual mobility component in the treatment of displaced intracapsular fractures of the proximal femur: Can a trial investigating total hip arthroplasty for hip fracture be delivered in the NHS?. Issue 10 (October 2016) - Huxley, C.; Achten, J.; Costa, M. L.; Griffiths, F.; Griffin, X. L.
Abstract : Objectives: The annual incidence of hip fracture is 620 000 in the European Union. The cost of this clinical problem has been estimated at 1.75 million disability-adjusted life years lost, equating to 1.4% of the total healthcare burden in established market economies. Recent guidance from The National Institute for Health and Clinical Excellence (NICE) states that research into the clinical and cost effectiveness of total hip arthroplasty (THA) as a treatment for hip fracture is a priority. We asked the question: can a trial investigating THA for hip fracture currently be delivered in the NHS? Methods: We performed a contemporaneous process evaluation that provides a context for the interpretation of the findings of WHiTE Two – a randomised study of THA for hip fracture. We developed a mixed methods approach to situate the trial centre within the context of wider United Kingdom clinical practice. We focused on fidelity, implementation, acceptability and feasibility of both the trial processes and interventions to stakeholder groups, such as healthcare providers and patients. Results: We have shown that patients are willing to participate in this type of research and that surgeons value being part of a team that has a strong research ethos. However, surgical practice does not currently reflect NICE guidance. Current models of service delivery for hip fractures are unlikely to be able to provide timely total hip arthroplasty for suitable patients. Conclusions: Further observational research should be conducted to define the population of interest before future interventional studies are performed. Cite this article: C. Huxley, J. Achten, M. L. Costa, F. Griffiths, X. L. Griffin. A process evaluation of the WHiTE Two trial comparing total hip arthroplasty with and without dual mobility component in the treatment of displaced intracapsular fractures of the proximal femur: Can a trial investigating total hip arthroplasty for hip fracture be delivered in the NHS? Bone Joint Res 2016;5:444–452. DOI: 10.1302/2046-3758.510.BJR-2015-0008.R1.